Social Security, Medicare & government pensions : get the most out of your retirement & medical benefits - Matthews, J. L., 1946- (Nolo Law for All, 2026)
"This book helps baby boomers navigate the Medicare and Social Security systems and maximize their benefits, and, if they need to, appeal denials of services and benefits. The book also explains Social Security disability, veterans disability compensation, and federal retirement benefits, as well as SSI, Medicaid, and the VA pension for readers with low income." --